Strategic intent, organizational environment, and organizational learning mechanisms: a multiple-case study in the construction industry in Taiwan. Issue 5 (1st August 2016) - Fang, Shih-Chieh; Chen, Hung Ku
Abstract : Purpose: The purpose of the current study is to develop different kinds of organizational learning mechanisms based on various types of strategic intents (proactive- and reactive- orientation) and organizational environments (stable and unstable). Design/methodology/approach: We utilized a grounded theory approach, and corroborated our results using multiple interviews and documents related to various cases. We determined the inter-judge agreement and performed a composite reliability analysis to ensure the robustness of our research. Findings: Successful organization learning is contingent upon managerial strategic intent and the organizational environment in which the organization operates. Proactive strategic intent will cultivate a group-oriented learning system, whereas reactive strategic intent emphasizes the effectiveness of personal learning. Firms in an environment marked by radical change utilize experiential learning mechanisms (Participation- and Experience-orientation), whereas firms in a stable environment use a specialist-knowledge-oriented approach to learning (Benchmarking- and Specializing -orientation). Originality/value: We offer a theoretical framework two-by-two matrix that has practical implications in providing managers with guidance in selecting the appropriate organizational learning mechanism to implement in their firms.